Antihero Care: On Fieldwork and Anthropology. Issue 2 (29th October 2020) - Yates‐Doerr, Emily
Summary: "Antihero care" offers an approach to anthropology that emphasizes the importance of fallibility over mastery and social connections over individually acquired knowledge. I draw together Le Guin's Carrier Bag Theory of Fiction and Mol, Pols, and Moser's Care in Practice to analyze the challenge of carrying out fieldwork with my children in highland Guatemala. I describe how an everyday accident led me to refuse the "killer story" of the hero and to instead embrace a script that emphasized dependency and incompletion. In my case, antihero care has changed the way I engage with holism and biomedicine in my research and writing. More broadly, reframing limitations on knowledge as a strength—not a drawback—of the discipline usefully unsettles the boundaries between fieldwork and care work.